Progam Klinik Makhroj Bagi Santri Madrasah Diniyah Al-Ichsan Petungombo Sepawon Plosoklaten Kediri - Faiz Khoiruloh; Muhammad Faiz Amiruddin (LP3M IAIFA Kediri, 2020)
Lack of teachers is a major problem at MADIN Al-Ichsan petungombo. This problem has a considerable impact on the understanding of students in understanding the material in MADIN Al-Ichsan petungombo, especially in the field of makhorijul qur'anic letters. At least the duration of the teacher to make students learn makhorijul qur'an is very minimal because studying the material must be done intensively. Therefore, researchers apply the talaqi method to facilitate and familiarize students when learning the makhorijul of quranic letters because of the exact methods that are used for children of petungombo hamlets with this method. The author uses research methods to collect data, including learning makhorijul letter methods used is the talaqi method to easily develop from makhorijul letter of the Quran. The equipment used for learning is only whiteboards, chalk, and erasers. With the application of learning makhorijul letters of the Qur'an children are facilitated to understand about the material makhorijul letters and facilitate reading by considering various readings of letters and punctuation in the Qur'an.